Gugatan Pembatalan Perkawinan Yang Dinyatakan Tidak Diterima Akibat Penetapan Itsbat Nikah Antara Suami Dengan Istri Kedua Ditinjau Dari UU Perkawinan dan Hukum Acara Perdata (Studi Kasus Putusan Nomor 343/Pdt.G/2023/PTA.Sby) - Rambe, Fitri Hanum; Djanuardi, Djanuardi; Rachmainy, Linda (Media Hukum Indonesia (MHI), 2024)
Polygamous marriage in Indonesia can be carried out by fulfilling the requirements stipulated in the legislation. However, if these requirements are not met, the marriage can be annulled. The Surabaya High Court Decision No. 343/Pdt.G/2023/PTA.Sby is one such decision regarding a lawsuit for the annulment of a marriage filed by the first wife against her husband's polygamous marriage with the second wife, which was conducted without the consent of the lawful first wife. The decision stated that the lawsuit could not be accepted because the marriage proposed for annulment had already been dissolved due to death. This study aims to understand the basis for the lawsuit to annul the second marriage and the legal consequences on the status of the second marriage from the perspective of the Marriage Law and Civil Procedure Law. The author conducted this research using a normative juridical approach with a descriptive-analytical research specification. Data collection techniques were carried out through literature studies that gathered primary, secondary, and tertiary legal materials. The data analysis method was conducted through a normative qualitative method to address the legal issues in this study. Based on the research results, it can be concluded that the basis for the lawsuit to annul the second (polygamous) marriage did not meet the marriage requirements stipulated in Article 3 paragraph (2) of the Marriage Law, which states that a person engaging in polygamy must have the consent of the parties concerned. Furthermore, the legal consequence of the Surabaya High Court Decision No. 343/Pdt.G/2023/PTA.Sby, which stated that the lawsuit could not be accepted because the marriage had been dissolved due to death, is that the second marriage existed (was valid) along with its legal consequences.